Remaja, Teknologi, dan Iman: Pendidikan Kristen Sebagai Kompas Spiritualitas Digital - Kezia Sindi Trisani; Esti Regina Boiliu; Reni Triposa (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2025)
This study aims to critically identify and analyze the role of Christian education in shaping and sustaining the spiritual discipline of Christian youth in the digital age. Amid the rapid development of technology, today’s adolescents live in an environment filled with instant access to information and virtual interactions, which may reshape their understanding and practice of faith. This research employs a qualitative method with a literature study approach, analyzing various academic sources and relevant studies. The findings indicate that digital technology, when managed wisely, can serve as an effective tool for faith education—through social media, spiritual apps, and interactive online learning. However, excessive reliance on technology without proper guidance may result in a weakened connection to faith communities and diminished depth in personal spirituality. Therefore, Christian education is challenged to design a balanced approach between the use of digital media and the strengthening of interpersonal relationships within the church community. The novelty of this research lies in its formulation of a digitally based pedagogical strategy that preserves the core of Christian spirituality, offering a relevant response to the spiritual formation needs of youth in an ever-evolving digital culture.